A cristianização da fides romana no sermão XII de São Cesário de Arles : do crer ao fazer latino-português - Figueiredo, Jandyra Gonçalves (2007)
San Cesario di Arles (470 - 542), in the Psalm XII, preached about the Christian faith, emphasizing that its value is based in the deeds of its works. His argument relies in the Christianization of the etymological ties between fides and fit establishing a semantic and theologic unit between the belief and the deed, in order to prove the biblical truth that faith without deeds is dead. This work required a preliminary research about etymology, semantics as well as classic and Christian Latinate. It was followed by the development of the study of the affinity of uerba credendi and uerba faciendi, from Latin to contemporary Portuguese, in samples gathered from cesarian texts.